How to learn and teach in medical school : a learner-centered approach - Quirk, Mark E. (Charles C Thomas, 1994)
This book can be used by students, faculty, and administrators to enhance the process of medical education. Medical students can use it to develop and refine their learning skills, assess their individual learning needs, identify resources to meet these needs, and to prepare themselves for critical learning events and transitions. Faculty can use this book to understand the learning process and develop teaching skills, thereby providing a framework for critically assessing how they teach. Administrators can use it to expose inadequacies in the medical education process and to strengthen the te.